Penerapan Pembelajaran Futurisktik pada Pendidikan Islam - Budiono, Slamet; Sugiyarti, Sri; Sanusi, M. (Al-DYAS, 2024)
This This article discusses the application of futuristic learning to Islamic education. The aim is to find out the extent to which the futuristic learning model is implemented while maintaining the basic principles of Islamic education. This research uses a literature review approach from several book sources, journal articles and websites. The results of the research show that futuristic learning is applied proportionally, pays attention to all aspects of students and does not overdo the use of digital learning media, is able to bring a progressive mindset to students, is not left behind with the times, but is also not easily carried away by the current of the times and infected with addiction. digital. Of course, with strict control and supervision, both from parents and teachers. Without abandoning the basic principles and objectives of Islamic education, the most important capital for students to face the times in the future, with their behavior, whatever their various names, then Muslims have confidence, that with the principle of holding fast to the rope of Allah subhanahu wa ta'ala, in the form of the Qur'an and Sunnah, humans will not be lost forever.